A Historical Analysis on the Experience of Forming Institutions in Nanotechnology Management in Iran - Meysam Narimani; Mohsen Mohammadi (بهبود مدیریت, 2021)
One of the important issues of industrial and technology policy is the position of the policy-making institution in the structure of the political system and its role in relation to the traditional policy-making structure. The experience of Iran's entry into nanotechnology policy-making deserves special attention, both in terms of specialized entry into a technological as well as the impact of nano-related policies on the country's industrial and technological policies. First it is noteworthy that the experience of the Nano Council has historically preceded the formation of the Vice-Presidency for Science and Technology and other technology development councils. It is also important to pay attention to the impact of the policy infrastructure of the Nano council on other industrial and technological policy such as the Iranian Making Exhibition (iranlabexpo), the Patent Office, Elites Federation and the national laboratory network. Therefore, this article delves into the historical experience of Iran over past two decades in nanotechnology policy (since the beginning of the 2000s), focusing on the formation and development of the Iran Nanotechnology Council. Accordingly, while collecting and analyzing written data such as reports, news and public interviews, we conducted semi-structured interviews with the founders and key people engaged in the formation and development of the council. Core categories in the historical analysis of nanotechnology policy-making experience are training policy-making experts, creating institutions for implementing specialized programs, managerial stability and flexibility in operations and supports. In other words, the success of the Nano Council, has to do with the support of high-ranking officials and the presence of related institutions as a supporting and strengthening structure along with conflict management with stakeholders.